A Lot of Cyber Fizzle But Not A Lot of Bang: Evidence about the Use of Cyber Operations from Wargames. Issue 2 (25th April 2022) - Schneider, Jacquelyn; Schechter, Benjamin; Shaffer, Rachael
Abstract: Despite a burgeoning focus on cyber and international security, there is still great debate about how cyber operations fit among other military and foreign policy means. Are they a substitution option—a way to create similar effects with different, potentially less risky, means? Or are they a support to other means, meant to enable and increase the efficacy of military operations and foreign policy options? Finally, are they a new complement to existing means—a unique way to influence, coerce, and derive military outcomes? The answer to these questions is significant because how cyber operations are used has implications for crisis stability as well as the ways wars are fought. In order to test these theories of cyber and state power, we use a crisis wargame that examines the use of cyberspace operations across a game series played over two years with 500+ players. We find that, despite a general increase in focus within the game on cyber operations, these operations still have little influence on the overall violence of the crises. Instead, cyber operations are primarily used to shape narratives as a complement to diplomacy prior to war and then as a support to military operations after war has escalated. Cyber operations, therefore, show an increasing and important amount of fizzle but not a lot of bang.